Eurekan faults on northern Ellesmere Island, Arctic Canada: from Cenozoic strike-slip tectonics to recent seismicity ... - Brandes, Christian; Piepjohn, Karsten (Amsterdam [u.a.] : Elsevier Science, 2021)
The Eurekan deformation is a partially contractional Cenozoic tectonic event that affected large parts of the Arctic region. In the study area on northern Ellesmere Island, major NE-SW trending strike-slip faults occur, which are related to the Eurekan deformation. The outcrop data show that left-lateral strike-slip kinematics slightly dominate, but also right-lateral kinematics were documented. Cross-cutting relationships of the individual faults give evidence for multiple fault reactivations within major strike-slip zones. The reconstructed paleostress fields show two phases. The first phase started with a N-S compression and shifted over a NNE-SSW compression into a NNW-SSE compression. The second phase was a WNW-ESE compression. The paleostress field evolution reflects the movements of Greenland. During the Eurekan phase 1, Greenland moved northward and during Eurekan phase 2 it moved to the WNW. These motions likely controlled the stress field on northern Ellesmere Island. From the paleostress field ...